Superstructures with Atomic-Level Arranged Perovskite and Oxide Layers for Advanced Oxidation with an Enhanced Non-Free Radical Pathway - Yang, L.; Jiao, Y.; Xu, Xiaomin; Pan, Y.; Su, Chao; Duan, Xiaoguang; Sun, Hongqi; Liu, Shaomin; Wang, Shaobin; Shao, Zongping (AMER CHEMICAL SOC, 2022)
Perovskite-based oxides demonstrate a great catalytic efficiency in advanced oxidation processes (AOPs), where both free and non-free radical pathways may occur. The non-free radical pathway is preferable because it is less affected by the wastewater environment, yet little is known about its origin. Here, we exploit Ruddlesden-Popper (RP) layered perovskite oxides as an excellent platform for investigating the structure-property relationship for peroxymonosulfate (PMS) activation in AOPs. The atomic-level interaction of the perovskite and rock salt layers in RP oxides stabilizes the transition metals at low valences, causing the formation of abundant lattice oxygen/interstitial oxygen species. Unlike oxygen vacancies in conventional perovskites, which promote free-radical generation, these reactive oxygen species in RP perovskites have high activity and mobility and facilitate the formation of non-free radical singlet oxygen. This singlet oxygen reaction pathway is optimized by tailoring the oxygen species, leading to the discovery of LaSrCo0.8Fe0.2O4 with exceptionally efficient PMS activation.